Semiotic Analysis and Mise En Scene Concept of Ancient Javanese Rituals in the Film BITING (2021) - Nisrina Firdaus; Pandu Watu Alam (Cinematology: Journal Anthology of Film and Television Studies, 2022)
This article describes the semiotic analysis and the concept of mise en scene of ancient Javanese rituals in the film Biting (lidi). This film is interesting to study because the concept of ancient Javanese rituals is presented as a spectacle that can educate the public about the myths prevailing in ancient Javanese ritual culture. In addition, the concept of the existence of images presented adequately represents the essence of ancient Javanese culture through costumes, make-up, dialogue, settings. Location, artistic, camera position and lighting. This is the aim of research on reading signs and markers as well as the concept of mise en scene. A qualitative method with a semiotic approach and the concept of mise en scene is used in analyzing this film. This study found that all elements of semiotics starting from the meaning of denotation, connotation and myth are clearly visible in every scene. The concept of mise en scene can also be seen clearly depicting the appropriateness of the ancient Javanese rituals in each scene. The implications of this research can be a reference for researchers in analyzing ancient Javanese rituals in particular and other cultural structures in a film.